Persepsi Mahasiswa Terhadap Pemberitaan Vaksinasi Covid-19 Pada Media Sosial Instagram - Rista Dwi Lestari; Dina Safira Putri; Dwi Nuning Anggraeny; Ririn Puspita Tutiasri (Institute of Social and Political Science Jakarta (Institut Ilmu Sosial dan Ilmu Politik Jakarta - IISIP Jakarta), 2021)
The Covid-19 vaccination activity in Indonesia at the end of 2020 caused a new polemic in the community and gave rise to various positive and negative opinions about vaccination. Experts and public figures explain the importance of vaccinating Covid-19 through their social media accounts. Social media became a medium at the current covid-19 pandemic to share information and policies on Covid-19. The study discussed students’ perceptions in Surabaya of the Covid-19 vaccination information on Dr. Tirta’s social media account. We conducted this study with a qualitative approach and online data-collection technique for interviews with eight student informers over 20-26 years. Studies show that six out of eight informers claim that postings about vaccinations on Dr. Tirta’s Instagram account have significantly been affected by information coupled with accurate data. Dr. Tirta’s covid-19 vaccination information on the student’s Instagram account has a powerful influence on a student’s perception of the Covid-19 vaccination and can transform a student’s actions by willingly vaccinating a Covid-19.